Analisis Hukum Pidana dan Strategi Pemulihan Aset dalam Kasus Penggelapan Uang Perusahaan - Mabsus, Muhammad Irfan Fadilla; Jatmiko, Gunawan; Tamza, Fristia Berdian (Indonesian Journal Publisher, 2025)
This study aims to analyze the application of criminal law to corporate embezzlement cases and formulate effective asset recovery strategies within the Indonesian legal framework. Corporate embezzlement is a serious crime that not only causes financial losses but also disrupts business stability and undermines public trust. This research employs a normative legal method, conducting an in-depth analysis of criminal law provisions, theories of criminal liability, and asset recovery mechanisms based on literature review and empirical data. The findings indicate that the main challenges in addressing embezzlement cases include the complexity of perpetrators' modus operandi, weak internal corporate oversight, and the lack of regulatory harmonization among law enforcement agencies. Asset recovery strategies, such as asset tracing and confiscation, remain suboptimal due to technological limitations and ineffective inter-agency coordination. Therefore, strengthening regulatory harmonization, enhancing law enforcement training in asset-tracing technology, and improving corporate internal control systems are essential. Additionally, international cooperation must be reinforced to expedite the recovery of assets transferred abroad. This study contributes to public policy development and legal practices aimed at fostering a more secure and reliable business environment in Indonesia.